Black Tea Waste as Corrosion Inhibitor for Carbon Steel in 0.5 M HCl Medium - Meyliana Wulandari; Zahratussaadah Zahratussaadah; Nofrizal Nofrizal; Pandian Bothi Radja; Andreas Andreas (Indonesian Journal of Chemistry, 2023)
Indonesian black tea (BT) waste was utilized as a green corrosion inhibitor for carbon steel (CS) corrosion in a 0.5 M HCl medium. The BT extract was characterized using Fourier transform infra-red. The corrosion inhibition evaluation was studied using conventional weight loss methods, potentiodynamic polarization, and electrochemical impedance spectroscopy (EIS). Further, scanning electron microscopy-energy dispersive X-ray was applied to analyze the surface morphology of pure CS before and after contact with the inhibitor extract. After the addition of inhibitors, CS surface showed a better morphological transformation. The effect of oxygen contamination has also been studied in this research. The corrosion measurements of weight loss, potentiodynamic polarization, and EIS showed that the %IE BT extract was 84.70; 70.00; 72.80% at 0.20 g/L of inhibitor concentration. Adsorption isotherm studies have determined the reaction mechanism between the CS and inhibitor; in which the adsorption follows Langmuir. Gibbs free energy for the three methods is −16.62; −25.34; −24.35 kJ/mol, indicating electrostatic interaction (physisorption) between the metal surface and inhibitor. SEM and focus ion beam show that oxygen contamination can increase the corrosion rate resulting in CS damage. It shows that tea waste products can be used as an alternative corrosion inhibitor.